Expression of Fas Ligand is Higher in Early Stage Cervical Cancer with Lymph Nodes Metastasis - Irwanto, Yahya (Indonesian Socety of Obstetrics and Gynecology, 2012)
Objective: To know whether the expression of Fas Ligand has correlation with incidene of metastasis of pelvic lymph node and lymph-vascular stromal invasion (LVSI). Methods: All patients diagnosed of cervical cancer stage IB or IIA who underwent radical hysterectomy in Dr. Cipto Mangunkusumo Central General Hospital from January 2008 until December 2009 were included in analytic cross sectional study. We tested expression of Fas Ligand in cervical cancer specimen by immunohystochemistry with monoclonal antibody. The expression of Fas Ligand was compared between the group of patients with a positive and negative pelvic lymph node and between LVSI positive and negative. The difference of expression in both group were statistically analized with Chi-square test and the correlation Spearman test. Result: Ninety one patients underwent radical hysterectomy for two years and 43 patients were included in these study. The expression of Fas Ligand in 7 patients (16.3%) were negative and the others were positive, with weak, moderate and strong expression were 4 (9.3%), 27 (62.8%), and 5 (11.6%) respectively. The expression of Fas Ligand was significantly higher in the group of patients with positive pelvic lymph node compared to the group of the patients with negative pelvic lymph node (p=0.007) but there was no significant difference between group of the patients with LVSI positive and negative. With Spearman test, we found that the expression of Fas Ligand had a strong correlation with pelvic lymph nodes metastasis (coeff. correlation=0.519 and p=0.00) and have no correlation with LVSI (coef. corellation=0.112 and p=0.474). Conclusion: These finding suggested that expression of Fas Ligand in cervical cancer patients has a strong correlation with the incidence of pelvic lymph node metastasis and none with LVSI. [Indones J Obstet Gynecol 2012; 36-4: 194-9] Keywords: cervical cancer, fas ligand, immunohystochemistry, LVSI, pelvic lymph node metastasis